Metabolite identification of ibuprofen biodegradation by Patulibacter medicamentivorans under aerobic conditions. Issue 4 (10th February 2020) - Salgado, Ricado; Brito, Dulce; Noronha, Joao P.; Almeida, Barbara; Bronze, Maria R.; Oehmen, Adrian; Carvalho, Gilda; Barreto Crespo, Maria T.
ABSTRACT: Ibuprofen (IBU) is a non-steroidal anti-inflammatory drug that is becoming increasingly recognized as an important micropollutant to be monitored in wastewater treatment plants (WWTP), since it has been detected in effluents at the µg L −1 level. The IBU metabolites from biological degradation are not completely understood and can represent a threat to natural aquatic systems. P. medicamentivorans was previously isolated from WWTP sludge and found to be capable of IBU degradation. The aerobic biodegradation of ibuprofen by this organism was investigated in a batch lab-scale reactor for the identification of the metabolites formed. The metabolites were analysed and putatively identified by HPLC-DAD-MS/MS and GC-MS and biodegradation pathways were proposed. The toxicity and the biodegradability potential of the metabolites were also investigated. The results showed that IBU biotransformation was achieved by hydroxylation followed by the formation of a carboxylic acid in the IBU molecule and by the formation of a catechol, allowing the aromatic ring cleavage. Two biodegradation pathways were proposed: in one, the metabolites generated from the enzymatic action correspond to a less biodegradable chemical structure of the intermediate products (isobutylbenzene and 3-isobutylphenol), with comparatively higher toxicity; in the other mechanism, more oxidable chemical structures were formed with less toxicity and higher biodegradability. This suggests that the biodegradation of IBU by P. medicamentivorans can take place by more than one mechanism regarding the enzymes formed by this Gram-positive bacterium, with subsequent oxidation of the parent compound to overall more soluble and less toxic compounds to fish, daphnia and green algae. GRAPHICAL ABSTRACT: